1983
DOI: 10.1016/0092-8674(83)90203-9
|View full text |Cite
|
Sign up to set email alerts
|

Generation of asymmetry and segregation of germ-line granules in early C. elegans embryos

Abstract: Germ-line granules in C. elegans embryos (P granules) can be visualized by immunofluorescence microscopy using a monoclonal antibody. In mutant zygotes with abnormal spindle orientations and in wild-type zygotes treated with the microtubule inhibitors nocodazole, colcemid, vinblastine, and griseofulvin, both P-granule segregation to the posterior pole and the concomitant pseudocleavage occur apparently normally, but the normally concurrent migration of the pronuclei is inhibited. Conversely, treatment of wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
353
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 524 publications
(358 citation statements)
references
References 25 publications
3
353
0
2
Order By: Relevance
“…We examined this response in C. elegans, by using nocodazole to destabilize microtubules in two-cell stage embryos (see Materials and Methods). In earlier studies, nocodazole was shown to largely, although not entirely, deplete spindle microtubules in dividing one-cell stage C. elegans embryos, without arresting mitosis (Strome and Wood, 1983;Hyman and White, 1987). Exposing onecell embryos to nocodazole produced variable effects (our unpublished data), possibly due to variability in the postfertilization age of one-cell embryos dissected from adults when exposed to this chemical.…”
Section: A Functional Spindle Checkpoint In the Early C Elegans Embryomentioning
confidence: 99%
See 1 more Smart Citation
“…We examined this response in C. elegans, by using nocodazole to destabilize microtubules in two-cell stage embryos (see Materials and Methods). In earlier studies, nocodazole was shown to largely, although not entirely, deplete spindle microtubules in dividing one-cell stage C. elegans embryos, without arresting mitosis (Strome and Wood, 1983;Hyman and White, 1987). Exposing onecell embryos to nocodazole produced variable effects (our unpublished data), possibly due to variability in the postfertilization age of one-cell embryos dissected from adults when exposed to this chemical.…”
Section: A Functional Spindle Checkpoint In the Early C Elegans Embryomentioning
confidence: 99%
“…Application of nocodazole at this time prevented the reformation of astral microtubules during the second cell division. Although in earlier studies the eggshell was cracked to introduce nocodazole into the early embryo (Strome and Wood, 1983), we have found that nocodazole can effectively penetrate the early embryo eggshell without cracking, as determined by mispositioned mitotic spindles and the partial depletion of microtubules of one-and two-cell embryos (Kurz et al, 2002). Slides were overlaid with a 22 ϫ 22-mm glass coverslip and sealed with melted petroleum jelly.…”
Section: Nocodazole Treatmentmentioning
confidence: 99%
“…For antibody staining, worms were permeabilized by using the freeze-crack method, fixed for 10 min in methanol and 10 min in acetone, and stained as described (38). Antibody dilutions were 1:30,000 rabbit anti-PGL-1 (26), 1:500 guinea pig anti-HTP-3 (39), 1:50,000 rat anti-PGL-3 (40), 1:200 rabbit anti-CEH-18 (41), and 1:500 Alexa Fluor secondary antibodies (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Centrosome centration depends mostly on the microtubule cytoskeleton. 4,8 Because the centration depends on filamentous microtubules, the candidate mechanisms can be roughly divided into anticipated number of anchors to contact a single microtubule is proportional to the surface area covered by the microtubule, the force on a single microtubule should be roughly proportional to the squared length of the microtubule (L 2 ). 25 The assumption that the pulling force generator is limited in number is based on an experimental estimation.…”
mentioning
confidence: 99%